Chemical Composition and Sensory Profiles of Fermented Cocoa Beans Obtained from Various Regions of Indonesia - Ariza Budi Tunjung Sari; null Fahrurrozi; Tri Marwati; Titiek Farianti Djaafar; Retno Utami Hatmi; null Purwaningsih; Yeyen Prestyaning Wanita; Puspita Lisdiyanti; Urip Perwitasari; Ario Betha Juanssilfero; Endang Sutriswati Rahayu (International Journal of Food Science)
The chemical composition and sensory profile of cocoa beans are essential factors determining the quality of cocoa-based products. In this study, cocoa bean samples were collected from various regions of Indonesia, including Aceh, Banten, Bali, East Java, West Sumatra, West Sulawesi, East Kalimantan, and Yogyakarta. The cocoa beans were fermented and sun-dried according to the producers’ protocols and local practices. The sensory profile, fat content, total phenolic content, and the composition of sugars, organic acids, and amino acids of the cocoa bean samples were analyzed. The results revealed that the chemical composition and sensory profiles of the samples were diverse. The sensory profiles of cocoa liquor samples were described by low intensities of cocoa notes with the occurrence of fruity, floral, spicy, and sweet notes. The concentration of acetic acid, lactic acid, and some amino acids (glutamic acid, proline, and methionine) was associated with fresh fruit, browned fruit, and roasted note of the cocoa liquor, respectively. The variation in the environmental conditions and postharvest practices contributed to the diversity of cocoa beans’ chemical and sensory characteristics.